Eosinophil-derived COX-2 protects against experimental colitis through the PGE 2 –IL-22 axis - Yang Yang; Constance L. Atkins; Yuanyuan Fan; Lidan Hou; Jie Zhao; Junda Gao; Yankai Wen; Nicolas F. Moreno; Xiangsheng Huang; Faraz Bishehsari; Agnieszka K. Czopik; Sean P. Colgan; et al. (Proceedings of the National Academy of Sciences, 2026)
Inflammatory bowel disease (IBD) is driven by a breakdown in immune regulation and epithelial barrier function, yet the contribution of eosinophils to this process has remained poorly defined and controversial. While eosinophils infiltrate the intestinal mucosa during both flares and remission, their role in shaping disease outcomes is unclear. Our RNA-seq analyses of colonic eosinophils isolated from dextran sulfate sodium (DSS)-treated mice revealed a significant upregulation of cyclooxygenase (COX)-2 (gene name, Ptgs2 ). Eosinophil-specific deletion of COX-2 (Ptgs2 fl/fl eoCre +/− ) reduced IL-22 production and exacerbated DSS- and trinitrobenzene sulfonic acid (TNBS)-induced colitis, characterized by greater weight loss, higher disease activity, colon shortening, and epithelial injury. Administration of recombinant IL-22 reversed these phenotypes. Mechanistically, eosinophil-derived COX-2 enhanced IL-22 production by type 3 Innate lymphoid cells (ILC3s) through prostaglandin E2 (PGE 2 ) signaling. Consistently, Ptgs2 fl/fl eoCre +/− mice exhibited reduced colonic PGE 2 levels, while PGE 2 analog treatment restored IL-22 production and mucosal protection. Our findings identify eosinophil-derived COX-2 and PGE 2 as a critical regulator of IL-22 production during colitis, uncovering a eosinophil–ILC3 cross talk that safeguards the intestinal barrier and represents a promising therapeutic target in IBD.